Common neural responses to romantic rejection and acceptance in healthy adults. (2nd September 2020) - Hsu, David T.; Sankar, Anjali; Malik, Mohammad A.; Langenecker, Scott A.; Mickey, Brian J.; Love, Tiffany M.
ABSTRACT: Although romantic rejection and acceptance have a strong impact on mood in adults, their neural response patterns are relatively unexplored. The present study used functional magnetic resonance imaging (fMRI) to examine neural responses to romantic rejection and acceptance in 36 healthy men and women, ages 18–53 years. Activations during rejection showed extensive anatomical overlap with activations during acceptance in the ventrolateral prefrontal cortex (vlPFC) and anterior insula (AI). In an analysis of sex differences, men and women did not differ in behavioral responses; however, men showed greater activation to romantic rejection and acceptance in the left vlPFC and AI compared to women. The vlPFC and AI may play a role in social cognition, tuned to detect the intentions and feelings of others whether they are positive or negative. In the context of romantic rejection and acceptance, this activation may signal the intent of others who are desired by the individual, leading to changes in mood, self-esteem, and social motivation.